PENGARUH KUALITAS LAYANAN, HARGA, DAN LOKASI TERHADAP KEPUASAN PELANGGAN THE WINNER PREMIERE HOTEL PEMALANG (Studi pada pelanggan The Winner Premiere Hotel tahun 2015) - Widhi Setyawan Putranto, 12.05.51.0128; ., Kasmari (Students Journal of Economic and Management, 2016)
This study analyzed the effect of service quality, price, and location on customer satisfaction. This topics was taken because the new hotels that indicated the public interest on hotels in increased. So then, this research objects is The Winner Premiere Hotels Pemalang, Pemalang district. The population is all of the guest The Winner Premiere Hotels Pemalang at 2015 which amount 6153 guests. The sampling technique of this research is purposive sampling. Data collection methods is using quetionary by filling a list of statements to the respondents in collecting information. The purpose of this research is to find the answer of the plot that affect customer satisfaction. Data were analyzed using analysis of Kaiser-Meyer-Olkin (KMO) to test the validation of questions item, Cronbach Alpha formula to test the reliability instruments, regression analysis to test the effect of partially or simultaniously independents variables on dependents variables. The results of the research are : (1) Quality of Service has a positive and significant impact on customer satisfaction . (2) Price has a positive and significant impact on customer satisfaction . (3) The location has a positive and significant impact on customer satisfaction.Keywords : Quality Service, Price, Location, Customer Satisfaction.